Carbolong chemistry: nucleophilic aromatic substitution of a triflate functionalized iridapentalene. Issue 68 (4th August 2021) - Li, Jinhua; Lu, Zhengyu; Hua, Yuhui; Chen, Dafa; Xia, Haiping
Abstract : The nucleophilic aromatic substitution (SN Ar) reactions of a triflate functionalized iridapentalene with C -, N -, O - and S -centred nucleophiles afforded a series of irida–carbolong derivatives. Abstract : The reactivity of the triflate functionalized iridapentalene 1, [Ir{CHC(CH2 C(CO2 Me)2 CH2 ){CC{CHC(OTf){CH(CO)(PPh3 )2 ]OTf, with C -, N -, O - and S -centered neutral nucleophiles was studied, leading to the isolation of a wide array of irida–carbolong derivatives. As an extension, a polycyclic complex with a rare six-fused-ring structure was constructed. This strategy provides a new route for the construction of functionalized metallaaromatic complexes, and the resulting iridacycles exhibit broad spectral absorption ranges, making them potential photoelectric materials.